2014
DOI: 10.1093/neuonc/nou043
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional diversity of long-term glioblastoma survivors

Abstract: While IDH mutant proneural tumors impart a better prognosis in the short-term, survival beyond 4 years does not require IDH mutation and is not dictated by a single transcriptional subclass. In contrast, MGMT methylation continues to have strong prognostic value for survival beyond 4 years. These findings have substantial impact for understanding GBM biology and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 25 publications
10
52
1
4
Order By: Relevance
“…Recently, a pro-tumorigenic inflammation signature has been described for IDH wt STS [16]. In addition to confirming this finding, we have resolved these expression differences further.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, a pro-tumorigenic inflammation signature has been described for IDH wt STS [16]. In addition to confirming this finding, we have resolved these expression differences further.…”
Section: Discussionsupporting
confidence: 79%
“…A number of recent publications on the transcriptome of GBM LTS have assessed mesenchymal, proneural, classical and neural subtypes among their patient cohorts [16,46]. However, none of these studies validated differences in gene expression between LTS and STS in a larger number of tumors.…”
Section: Lts and Sts Expression Profiles Are Prognostic In Non-g-cimpmentioning
confidence: 99%
“…Interesting links in glioma to MDA-9/Syntenin-related signaling have emerged recently. Database expression profiles comparing long-term survivors (LTSs) of GBM (>48 mo) with short-term survivors (<12 mo) revealed a 40% decrease in IGFBP-2, a noted downstream product of MDA-9/Syntenin signaling (9), in LTS tumors (31). Additionally, identification of a radiosensitive gene signature via expression data from the NCI-60 cancer cell panel revealed that a recognized MDA-9/Syntenin binding partner, integrin-linked kinase (32), was significantly down-regulated in radiosensitive cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the next several years will produce multiple prospective trials to investigate novel combination therapies beyond anti-angiogenic therapies and dose escalation. The integration of rationally selected targeted agents after gaining an improved understanding of the genomic landscape of GBM will be critical to significantly improve outcomes[68]. …”
Section: Five-year Viewmentioning
confidence: 99%